PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL (Studi empiris pada karyawan Rumah Sakit Bhakti Asih Brebes) - Bela, Asoka Nusa (Faculty of Economics and Business Diponegoro University, 2014)
The large number of existing hospitals are at the core of the community, making the community has many options to do health care. There fore the leadership of the hospital and the soldiers must work together providing excellent service to it is maximum patient. Good relations between superiors and subordinate in the hospital an justice, then it would be increase organizational commitment of employees to the hospital. This research to find out how the influence of leader member exchange (LMX) and the organizational justice of organizational commitment.The research was carried out using multiple linear regression analysis wih the help of SPS program 21. The sample in this research are permanent employees of 63 respondent by the census method. Method of data collection in this research is through aqustionnaire distributed to 63 employees remain Bhakti Asih hospital in Brebess. Result of the analysis show that variable leader member exchange (LMX) influential organizational commitment to wards positif and influential organization justice positive variables of organizational commitment with the coefficient of determination Adjusted R Square shows the value of 0,552. The results of the determination of the contribution of leader member exchange (LMX) and justice organizationals in influencing organizational commitment 55,2% unted to 44,8% while the restis affected by other variables